A Comparative Study of Corporate Governance between Failed and Non-Failed Firms Evidenced from the Stock Exchange of Thailand - รักษาพงษ์ ศรัณย์พร; นาคประสิทธิ์ ชุติมา (KKBS Journal of Business Administration and Accountancy, 2019)
The objective of the study was to compare corporate governance between failed and non-failed firms listed on the Stock Exchange of Thailand (SET). The data were collected from the annual report and form 56-1 during 2006 to 2016. The samples were equally selected from firms being classified as failed firm status and from a matched-pair method of non-failed firm status totaling 54 pairs. The research instrument and hypothesis testing were descriptive statistics and univariate analysis. The results of the study showed that non-failed firms had unqualified opinion over failed firms. In addition, non-failed firms had a number of directors, remuneration for the board of directors and outsider ownership were statistically significant higher than failed firms.